Extracellular vesicles in the treatment of oxidative stress injury: global research status and trends - Zhang, Wenwen; Gan, Bin; Wang, Tingyu; Yang, Xiangjie; Xue, Yuanye; Zhong, Yuanqing; He, Xintong; Peng, Xinsheng; Zhou, Yanfang; Cheng, Xiaoyan (Frontiers in Molecular Biosciences, 2024)
The aim of this study was to conduct a bibliometric analysis of the literature on "Extracellular Vesicles in the Treatment of Oxidative Stress Injury" and to reveal its current status, hot spots and trends.The relevant literature was obtained from the Web of Science Core Collection (WoSCC) on April 29, 2023. We performed clustering and partnership analysis of authors, institutions, countries, references and keywords in the literature through CiteSpace software and the bibliometric online analysis platform and mapped the relevant knowledge maps.Results: A total of 1321 relevant publications were included in the bibliometric analysis, with the number of publications in this field increasing year by year. These included 944 "articles" and 377 "reviews". The maximum number of publications published in China is 512, and the maximum number of highly cited publications published in the United States is 20. Based on CiteSpace, the country collaboration network map shows close and stable collaboration among high-productivity countries. Based on WoSCC, there are 1706 relevant research institutions and 119 highly cited elite institutions, among which Kaohsing Chang Gung Men Hosp has the most extensive influence.Studies related to "Extracellular Vesicles in the Treatment of Oxidative Stress Injury" have been published in 548 journals. The keywords of the publications show the main research areas and breakthroughs. Based on WoSCC, the keywords of the research area "Extracellular Vesicles in the Treatment of Oxidative Stress Injury" were found to be as follows: exosome(s), extracellular vesicle(s), oxidative stress, inflammation, mesenchymal stem cells, apoptosis, microRNA (miRNA), mitochondria, biomarker, autophagy, angiogenesis and Alzheimer's disease. Analysis showed that "mesenchymal stem cells", "microRNA", "autophagy", "histology" and "therapeutic" emerged as highly explosive keywords.This study is the first to use visual software and data mining to assess the literature in the field of "Extracellular Vesicles in the Treatment of Oxidative Stress Injury". The research history, research status and direction in this field provide a theoretical basis for its scientific research.